Wybrane problemy wyceny firm medycznych - Zarzecki, Dariusz (Valuation of medical practices - selected problems, 2005)
The health care industry in Poland has undergone changes over the last few years (including privatization) in response to changing public, economic and insurer demands - but some things have remained the same. A number of unique factors affect a medical practice's value, that tends to be derived from both tangible and intangible assets (such as goodwill). This article investigates the key issues related to valuation of medical practices. There are many factors that make up the value of a medical practice. The weight assigned to the each factor varies from practice to practice. A valuation done by a valuation analyst can assist the physician/owner in accurately establishing either the sale price to an outside buyer or the buy-in of a new doctor/investor.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 460-468